Modified carboxylated polysaccharide compositions and uses thereof
By functionalizing carboxymethyl cellulose into water-soluble salts of monovalent and divalent cations, the problem of carboxymethyl cellulose reducing viscosity and water solubility during divalent cation replacement is solved, maintaining its biodegradability and improving its Performance of oral care products.
Patent Information
- Application Number
- CN202380043737.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-05
- Filing Date
- 2023-01-31
- Publication Date
- 2025-01-07
AI Technical Summary
When existing carboxymethyl cellulose is replaced by divalent cations, its viscosity and water solubility decrease, affecting its biodegradability and application performance.
By functionalizing carboxymethyl cellulose into water-soluble salts of monovalent cations and divalent cations, it is used to prepare oral care products such as mucosal adhesives, denture adhesives and toothpastes.
The high molecular weight functionalization of carboxymethyl cellulose is achieved, and its water-soluble and biodegradable properties are maintained, which improves the adhesion performance of mucosal adhesives and denture adhesives and the stability of toothpaste.
Smart Images

Figure CN119278233A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a modified carboxylated polysaccharide, in particular to a modified carboxymethyl cellulose (CMC), and more particularly to a modified carboxymethyl cellulose (CMC) composed of at least one monovalent (M + ) cation and at least one divalent (M ++ ) Water-soluble salt of cationically functionalized carboxymethyl cellulose (CMC) and its preparation method and application. Background Art
[0002] Carboxylated polysaccharides such as carboxymethylcellulose (CMC), carboxymethyl inulin, carboxymethyl guar gum or carboxymethyl starch are long chain polymers whose solubility characteristics depend on the average chain length, degree of polymerization (DP) and degree of substitution (DS). The average amount of hydroxyl groups replaced by sodium carboxymethyl ether groups at C2, C3 and C6 in the cellulose structure is represented by the DS value. As the molecular weight increases, the viscosity of CMC solutions increases. Sodium carboxymethylcellulose (NaCMC) is an anionic water-soluble polyelectrolyte with numerous applications in food, pharmaceuticals, personal care, home care, cosmetics, paper and other industries. Sodium CMC is inherently biodegradable or readily biodegradable at DS values of 0.7 and below. When the carboxymethyl groups on CMC are replaced by cations other than sodium, such as divalent cations such as calcium, magnesium, zinc, tin, etc., various property changes are generally observed, including but not limited to reduced viscosity and reduced water solubility.
[0003] “Effect of mono-and di-valent salts on the properties of carboxymethylcellulose hydrogel under irradiation technique” published in International Journal of Chemical Sciences, 627-634, 10(2) in January 2012 disclosed a study on the swelling properties and gel content of CMC hydrogels prepared by gamma irradiation in the presence of monovalent and divalent salts (NaCl and CaCl2).
[0004] US patent publication US2005 / 0032940 (assigned to HealthTech Corporation) discloses an adhesive denture adhesive comprising a water-soluble polymer comprising 0.1 wt % to 20 wt % calcium sulfate and 3 wt % to 60 wt % sodium carboxymethylcellulose, wherein the sodium carboxymethylcellulose is used to form a gel by reacting with the calcium sulfate when in contact with an aqueous component.
[0005] The present inventors disclose herein a high molecular weight modified polysaccharide, in particular a modified carboxymethyl cellulose, wherein the carboxymethyl cellulose is composed of at least one monovalent cation (M + ) and at least one divalent cation (M ++ ) functionalization without compromising the water solubility and biodegradability of the substituted cellulose. Summary of the invention
[0006] The main aspect of the present application is to provide a modified carboxylated polysaccharide, in particular a modified carboxymethyl cellulose (CMC), wherein the modified carboxymethyl cellulose (CMC) is composed of at least one monovalent cation (M + ) and at least one divalent (M ++ ) A water-soluble salt of cationically functionalized carboxymethyl cellulose (CMC).
[0007] In another aspect, the present application provides a functionalized carboxymethyl cellulose (CMC) having the structure of (I):
[0008]
[0009] Among them, M + is a monovalent cation selected from the group consisting of sodium, potassium and lithium; M ++ is a divalent cation selected from the group consisting of calcium, magnesium, zinc, tin, copper and combinations thereof; and wherein n=2 to 500, M + = 0.1 wt % to 10 wt % of the carboxymethyl cellulose, M ++ = 0.1 wt % to 10 wt % of the carboxymethyl cellulose.
[0010] In another aspect, the functionalized carboxymethyl cellulose is selected from the group consisting of: (i) sodium calcium carboxymethyl cellulose (Na + -Ca ++ -CMC), (ii) sodium magnesium carboxymethyl cellulose (Na + -Mg ++ -CMC), (iii) sodium zinc carboxymethyl cellulose (Na + -Zn ++ -CMC), (iv) sodium calcium zinc carboxymethyl cellulose (Na + -Ca ++ -Zn ++ -CMC), (v) sodium carboxymethyl cellulose calcium magnesium (Na + -Ca ++ -Mg ++ -CMC), (vi) sodium magnesium zinc carboxymethyl cellulose (Na + -Mg ++ -Zn ++-CMC), (vii) sodium tin carboxymethyl cellulose (Na + -Sn ++ -CMC), (viii) sodium carboxymethyl cellulose calcium tin (Na + -Ca ++ -Sn ++ -CMC), (ix) sodium carboxymethyl cellulose magnesium tin (Na + -Mg ++ -Sn ++ -CMC), or (x) sodium zinc tin carboxymethyl cellulose (Na + -Zn ++ -Sn ++ -CMC).
[0011] In another aspect, the present application provides a mucoadhesive composition comprising: (i) (a) 0.1 wt % to 60 wt % of at least one monovalent (M + ) cation and at least one divalent (M ++ ) a water-soluble salt of a cationically functionalized carboxymethyl cellulose (CMC), or (b) 0.1 wt % to 60 wt % of (b1) composed of at least one monovalent (M + ) cation and at least one divalent (M ++ ) a water-soluble salt of a cationically functionalized carboxymethyl cellulose (CMC) and (b2) at least one monovalent (M + ) a water-soluble salt of a cationically functionalized carboxymethyl cellulose (CMC); (ii) 0.1 wt % to 60 wt % of a maleic acid or maleic anhydride copolymer of a C1 to C4 alkyl vinyl ether and maleic acid or anhydride monomer, the copolymer being a substantially alternating structure of monomers and 50 wt % to 90 wt % of the acid moieties in the polymer being converted to metal salts or mixed salts; and (iii) 0.1 wt % to 80 wt % of at least one additional ingredient.
[0012] In another aspect, the present application provides a denture adhesive composition comprising: (i) (a) 0.1 wt % to 60 wt % of at least one monovalent (M + ) cation and at least one divalent (M ++ ) a water-soluble salt of a cationically functionalized carboxymethyl cellulose (CMC), or (b) 0.1 wt % to 60 wt % of (b1) composed of at least one monovalent (M + ) cation and at least one divalent (M ++ ) a water-soluble salt of a cationically functionalized carboxymethyl cellulose (CMC) and (b2) at least one monovalent (M +) a water-soluble salt of a cationically functionalized carboxymethyl cellulose (CMC); (ii) 0.1 wt % to 60 wt % of a maleic acid or maleic anhydride copolymer of a C1 to C4 alkyl vinyl ether and maleic acid or anhydride monomer, the maleic acid or maleic anhydride copolymer being a substantially alternating structure of monomers and 50 wt % to 90 wt % of the acid moieties in the polymer being converted to metal salts or mixed salts; and (iii) 0.1 wt % to 80 wt % of at least one additional ingredient.
[0013] In another aspect, the present application provides a toothpaste composition comprising: (i) (a) 0.1 wt % to 20 wt % of at least one monovalent (M + ) cation and at least one divalent (M ++ ) a water-soluble salt of a cationically functionalized carboxymethyl cellulose (CMC); or (b) 0.1 wt % to 20 wt % of (b1) composed of at least one monovalent (M + ) cation and at least one divalent (M ++ ) a water-soluble salt of a cationically functionalized carboxymethyl cellulose (CMC) and (b2) at least one monovalent (M + ) a water-soluble salt of a cationically functionalized carboxymethyl cellulose (CMC); (ii) 0.1 wt % to 60 wt % of an orally acceptable solvent or carrier selected from water, glycerol, polyethylene glycol, polypropylene glycol, sorbitol, PEG, ethylene oxide-propylene oxide polymers, or combinations thereof; and (iii) 0.1 wt % to 20 wt % of a polymer of an orally acceptable monomer, including but not limited to maleic anhydride, maleic acid, C1 to C4 alkyl vinyl ether, alkylene oxides (alkylene oxides), ... oxides), alkyl lactams, triglycerides, animal or vegetable oils, or combinations thereof; and (iv) 0.1 wt % to 80 wt % of additional ingredients, including but not limited to abrasives selected from the group consisting of silica, calcium carbonate, calcium bicarbonate, sodium carbonate, sodium bicarbonate, and combinations thereof, antimicrobial agents, antiplaque agents, antitartar agents, antibiofilm agents, antisensitivity agents, antigingivitis agents, active substances selected from the group consisting of fluoride-providing compounds, dispersants, depositing agents, sealants, flavoring agents, foam enhancers, film-forming polymers, humectants, minerals, mouthfeel agents, peroxides, pH adjusters, preservatives, rheology modifiers, salts, sweeteners, colorants, whitening agents, surfactants selected from the group consisting of anionic surfactants, cationic surfactants, nonionic surfactants or zwitterionic surfactants, or combinations thereof, strain removal agents, antifouling agents, stabilizers, thickeners, vitamins, and zinc salts of organic and inorganic acids, or combinations thereof.
[0014] In another aspect, the present application provides a functionalized carboxymethyl cellulose obtained by an ion exchange method, the ion exchange method comprising (i) at least one monovalent (M + ) carboxymethyl cellulose salt and (ii) one or more divalent (M ++ ) metal salt reaction; wherein the divalent (M ++ ) Salt is selected from M ++ Chloride or M ++ Sulfate or M ++ The group of carbonates, in which the ion exchange product CMC has M + With M ++ The weight ratio is from about 1:75 to about 75:1.
[0015] In yet another aspect, the present application provides a method for preparing a monovalent-divalent (M + -M ++ ) a method for preparing carboxymethyl cellulose, the method comprising: (i) preparing (a) M ++ Chloride, M ++ Sulfate or M ++ carbonate and (b) an aqueous solution of a C2-C4 alcohol; (ii) adding sodium carboxymethyl cellulose (M + ), and stirring the resultant at ambient temperature for at least 30 minutes; (iii) filtering the resultant of step (ii) to obtain a wet cake; (iv) stirring the wet cake of step (iii) in a hydroalcoholic solution for at least 30 minutes; (v) repeating step (iv) at least 3 times to obtain pure M + -M ++ - a wet cake of carboxymethyl cellulose; (vi) drying the wet cake of step (v) in a fluidized bed dryer at 50°C to 70°C for at least 15 minutes to 30 minutes to obtain a dry M + -M ++ - carboxymethyl cellulose; and (vii) grinding the resultant of step (vi) to separate M + -M ++ -Dry powder of carboxymethyl cellulose. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In addition to the advantages and purposes cited in the present disclosure, one or more descriptions of the present disclosure briefly summarized may be supplemented with reference to certain embodiments shown in the accompanying drawings. These drawings constitute a part of the specification. However, it should be noted that the accompanying drawings illustrate preferred embodiments of the present disclosure and therefore do not limit its scope.
[0017] Figure 1 The sodium magnesium (Na + -Mg ++-CMC) of denture adhesive formulations (DA29 to DA31).
[0018] Figure 2 The sodium magnesium (Na + -Mg ++ -CMC) of denture adhesive formulations (DA29 to DA31).
[0019] Figure 3 The sodium calcium CMC (Na + -Ca ++ -CMC) of denture adhesive formulations (DA35 to DA38).
[0020] Figure 4 The sodium calcium CMC (Na + -Ca ++ -CMC) of denture adhesive formulations (DA35 to DA38).
[0021] Figure 5 The sodium calcium CMC (Na + -Ca ++ -CMC) of denture adhesive formulations (DA39 to DA42).
[0022] Figure 6 The sodium calcium CMC (Na + -Ca ++ -CMC) of denture adhesive formulations (DA39 to DA42).
[0023] Figure 7 The sodium calcium CMC (Na + -Ca ++ -CMC) of denture adhesive formulations (DA43 to DA46).
[0024] Figure 8 The sodium calcium CMC (Na + -Ca ++ -CMC) of denture adhesive formulations (DA43 to DA46). DETAILED DESCRIPTION
[0025] Before elaborating on at least one aspect of the disclosed and / or claimed inventive concept, it should be understood that the disclosed and / or claimed inventive concept is not limited in its application to the details of the construction and arrangement of the components or steps or methods described in the following specification or shown in the accompanying drawings. The disclosed and / or claimed inventive concept can be used in other aspects or practiced or implemented in a variety of ways. In addition, it should be understood that the words and terms used herein are for descriptive purposes only and should not be considered limiting.
[0026] Unless otherwise stated, the following terms used in accordance with the present disclosure shall be understood to have the following meanings.
[0027] Unless otherwise defined herein, the technical terms used in connection with the disclosed and / or claimed inventive concepts shall have the meanings commonly understood by those of ordinary skill in the art. In addition, unless the context otherwise requires, singular terms shall include plural terms and plural terms shall include the singular.
[0028] The singular indefinite articles ("a", "an") and definite articles ("the") include plural referents unless the context clearly dictates otherwise or the context of the reference clearly implies the contrary. The terms "comprising" and "comprises of" include more restrictive claims such as "consisting essentially of" and "consisting of".
[0029] For the purpose of the following detailed description, except in any operating examples or where otherwise indicated, the numbers expressing, for example, quantities of ingredients used in the specification and claims are to be understood as being modified in all instances by the term "about". The numerical parameters set forth in the specification and attached claims are approximations that may vary depending upon the properties desired in practicing the invention.
[0030] All percentages, parts, ratios and proportions used herein are by weight of the total composition, unless otherwise specified. All such weights as they pertain to listed ingredients are based on the active level and, therefore, do not include solvents or by-products that may be included in commercially available materials, unless otherwise specified.
[0031] All publications, articles, treatises, patents, patent publications, and other references cited herein are incorporated in their entirety for all purposes to the extent consistent with the disclosure herein.
[0032] The use of the term "at least one" will be understood to include one as well as any number more than one, including but not limited to 1, 2, 3, 4, 5, 10, 15, 20, 30, 40, 50, 100, etc. The term "at least one" can extend to 100 or 1000 or more, depending on the term it is connected to. In addition, an amount of 100 / 1000 should not be considered limiting, as lower or higher limits may also produce satisfactory results.
[0033] As used herein, the words "comprising" (and any forms thereof, such as the infinitive (comprise) and the third person singular (comprises), "having" (and any forms thereof, such as the infinitive (have) and the third person singular (has)), "including" (and any forms thereof, such as the third person singular (includes) and the infinitive (include)), or "containing" (and any forms thereof, such as the third person singular (contains) and the infinitive (contain)) are inclusive or open-ended, and do not exclude additional, unrecited elements or method steps.
[0034] As used herein, the term "degree of substitution" or "DS" relates to the average number of substituted hydroxyl groups per anhydroglucose unit.
[0035] As used herein, the term "monovalent cation" refers to a cation having a monovalence. Accordingly, the term "divalent cation" refers to a cation having a divalence. The monovalent cation is selected from the group consisting of sodium, potassium and lithium. Most preferably, the monovalent cation is sodium. The divalent cation is selected from the group consisting of calcium, magnesium, zinc, tin, copper and combinations thereof. More preferably, the divalent cation is calcium, magnesium, zinc and combinations thereof.
[0036] In a non-limiting embodiment, the present application provides a method comprising at least one monovalent (M + ) cation and at least one divalent (M ++ ) A cationically functionalized carboxylated polysaccharide. The polysaccharide is selected from the group consisting of carboxymethyl cellulose (CMC), carboxymethyl inulin, carboxymethyl guar gum and carboxymethyl starch.
[0037] As used herein, the term "functionalized" in relation to the "carboxylated polysaccharide" of the present application, particularly the carboxymethyl cellulose of the present application, refers to the presence of monovalent cations and one or more divalent cations on the polysaccharide or the carboxymethyl cellulose. A variety of monovalent cations and divalent cations can be introduced into the carboxymethyl cellulose by one or more functionalization reactions known to those of ordinary skill in the art. Non-limiting examples of functionalization reactions include ion exchange processes, which include (i) at least one monovalent (M + ) carboxymethyl cellulose salt and (ii) one or more divalent (M ++ ) metal salt reaction; wherein the divalent (M ++ ) Salt is selected from M ++ Chloride or M ++ Sulfate or M ++ carbonate group, wherein the final ion exchange carboxymethyl cellulose (CMC) polymer M + With M ++ The weight ratio is from about 1:70 to about 70:1.
[0038] Accordingly, the functionalized carboxylated polysaccharide is used in a variety of oral care compositions selected from mucoadhesive compositions, toothpaste / dentifogran compositions, oral treatment compositions, mouthwashes, and denture adhesive compositions.
[0039] In another non-limiting embodiment, the present application provides a functionalized carboxylated polysaccharide, a polysaccharide composed of at least one monovalent (M + ) cation and at least one divalent (M ++ ) A water-soluble salt of cationically functionalized carboxymethyl cellulose (CMC).
[0040] The term "functionalized carboxymethyl cellulose" refers to a cellulose composed of at least one monovalent (M + ) cation and at least one divalent (M ++ ) cation-functionalized low to medium molecular weight or medium to high molecular weight carboxymethyl cellulose (CMC), wherein the monovalent cation is selected from the group consisting of sodium, potassium and lithium, and the divalent cation is selected from the group consisting of calcium, magnesium, zinc, tin, copper and combinations thereof.
[0041] The carboxymethyl cellulose functionalized with at least one monovalent cation and at least one divalent cation has the structure (I):
[0042]
[0043] in,
[0044] M + is a monovalent cation selected from the group consisting of sodium, potassium, and lithium; and
[0045] M ++ is a divalent cation selected from the group consisting of calcium, magnesium, zinc, tin, copper, and combinations thereof; and
[0046] Where n≥2 to n≤2000, M + = 0.1 wt % to 10 wt % of the carboxymethyl cellulose, M ++ = 0.1 wt % to 7.5 wt % of the carboxymethyl cellulose.
[0047] In another non-limiting embodiment, the present application discloses a functionalized carboxymethyl cellulose comprising 0.1 wt % to 10 wt % of monovalent cations and 0.1 wt % to 10 wt % of one or more divalent cations. In another embodiment, the amount of the divalent cations is about 0.2 wt % to 7.5 wt % of the total CMC content.
[0048] In another non-limiting embodiment, the present application discloses that the monovalent cation (M) in the final functionalized CMC polymer + ) and divalent cations (M ++ ) by weight ratio of about 1:75 to about 75:1. In some embodiments, the final functionalized CMC polymer has M + With M ++ The weight ratio of M is about 1:3 to about 3:1, or about 1:5 to about 5:1, or about 1:10 to about 10:1, or about 1:20 to about 20:1, or about 1:30 to about 30:1, or about 1:40 to about 40:1, or about 1:50 to about 50:1, or about 1:60 to about 60:1, or about 1:70 to about 70:1. In another non-limiting embodiment, M + With M ++ The preferred weight ratio of is about 1:3 to about 3:1, or about 1:5 to about 5:1, or about 1:10 to about 10:1. In a preferred embodiment, the weight ratio of the monovalent cation to the divalent cation in the final functionalized CMC polymer is 75 to 1:1 to 75.
[0049] In another non-limiting embodiment, the present application provides a modified carboxymethyl cellulose (CMC), wherein the CMC is optionally further combined with at least one monovalent (M + ) cation-functionalized carboxymethyl cellulose (CMC) combination. Accordingly, the functionalized carboxymethyl cellulose having at least one monovalent cation has the structure (II):
[0050]
[0051] in,
[0052] M + is a monovalent cation selected from the group consisting of sodium, potassium and lithium; and wherein n≥2 to n≤2000, M + = 0.1 wt % to 10 wt % of the carboxymethyl cellulose.
[0053] In another non-limiting embodiment, the present application discloses a method comprising at least one monovalent (M + ) cation and at least one divalent (M ++ ) cationic biodegradable functionalized carboxymethyl cellulose (CMC). + ) cation is selected from the group consisting of sodium, potassium and lithium. ++ ) cation is selected from the group consisting of calcium, magnesium, zinc, copper, tin and combinations thereof. In addition, the functionalized carboxymethyl cellulose (CMC) may be in a dry powder form.
[0054] In another non-limiting embodiment, the degree of substitution of the functionalized carboxymethyl cellulose ranges from about 0.4 to about 0.5, or from about 0.5 to about 0.6, or from about 0.6 to about 0.7, or from about 0.7 to about 0.8, or from about 0.8 to about 0.9, or from about 0.9 to about 1.0, or from about 1.0 to about 1.1, or from about 1.1 to about 1.2. In a preferred embodiment, the degree of substitution ranges from about 0.4 to about 0.7. In another preferred embodiment, the DS of the modified cellulose is from about 0.4 to about 1.2.
[0055] In another non-limiting embodiment, the functionalized carboxymethyl cellulose of the present invention has a low molecular weight to medium molecular weight range or a medium molecular weight to high molecular weight range. The low molecular weight to medium molecular weight range refers to a functionalized carboxymethyl cellulose (CMC) with a weight average molecular weight of about 2,000 daltons to about 200,000 daltons. Similarly, the medium molecular weight to high molecular weight range refers to a functionalized carboxymethyl cellulose (CMC) with a weight average molecular weight of about 200,000 daltons to about 2,000,000 daltons.
[0056] In some embodiments, the average molecular weight range is from about 2000 Daltons to about 2,000,000 Daltons. In some embodiments, the molecular weight range is from about 10000 Daltons to about 15000 Daltons, or from about 15000 Daltons to about 20000 Daltons, or from about 20000 Daltons to about 300000 Daltons, or from about 30000 Daltons to about 40000 Daltons, or from about 40000 Daltons to about 50000 Daltons, or from about 50000 Daltons to about 60000 Daltons, or from about 60000 Daltons to about 70000 Daltons, or from about 70000 Daltons to about 80000 Daltons. In some embodiments, the molecular weight range is from about 80,000 Daltons to about 90,000 Daltons, or from about 90,000 Daltons to about 100,000 Daltons, or from about 100,000 Daltons to about 200,000 Daltons, or from about 200,000 Daltons to about 300,000 Daltons, or from about 300,000 Daltons to about 400,000 Daltons, or from about 400,000 Daltons to 500,000 Daltons. , or about 500,000 daltons to 600,000 daltons, or about 600,000 daltons to 700,000 daltons, or about 700,000 daltons to 800,000 daltons, or about 800,000 daltons to 900,000 daltons, or about 900,000 daltons to 1,000,000 daltons, or about 1,000,000 daltons to 1,100,000 daltons. In a preferred embodiment, the weight average molecular weight range of the functionalized carboxymethyl cellulose is 2000 daltons to 1,500,000 daltons. In another preferred embodiment, the weight average molecular weight range of the functionalized carboxymethyl cellulose is 80,000 daltons to 1,300,000 daltons.
[0057] Accordingly, the functionalized carboxymethyl cellulose (CMC) is biodegradable.
[0058] In another non-limiting embodiment, the functionalized water-soluble carboxymethyl cellulose is selected from the group consisting of: (i) sodium calcium carboxymethyl cellulose (Na + -Ca ++ -CMC), (ii) sodium magnesium carboxymethyl cellulose (Na + -Mg ++ -CMC), (iii) sodium zinc carboxymethyl cellulose (Na + -Zn ++ -CMC), (iv) sodium calcium zinc carboxymethyl cellulose (Na + -Ca ++ -Zn ++ -CMC), (v) sodium carboxymethyl cellulose calcium magnesium (Na+ -Ca ++ -Mg ++ -CMC), (vi) sodium magnesium zinc carboxymethyl cellulose (Na + -Mg ++ -Zn ++ -CMC), (vii) sodium tin carboxymethyl cellulose (Na + -Sn ++ -CMC), (viii) sodium carboxymethyl cellulose calcium tin (Na + -Ca ++ -Sn ++ -CMC), (ix) sodium carboxymethyl cellulose magnesium tin (Na + -Mg ++ -Sn ++ -CMC) or (x) carboxymethyl cellulose sodium zinc tin (Na + -Zn ++ -Sn ++ -CMC). In addition, the sodium carboxymethyl cellulose (Na + -CMC) can be combined with at least one functionalized carboxymethyl cellulose (CMC) selected from the above-mentioned CMC monovalent salt and divalent salt combination.
[0059] In another non-limiting embodiment, the functionalized water-soluble carboxymethyl cellulose is selected from the group consisting of: (i) calcium carboxymethyl cellulose potassium (K + -Ca ++ -CMC), (ii) potassium magnesium carboxymethyl cellulose (K + -Mg ++ -CMC), (iii) carboxymethyl cellulose potassium zinc (K + -Zn ++ -CMC), (iv) carboxymethyl cellulose potassium tin (K + -Sn ++ -CMC), (v) carboxymethyl cellulose potassium calcium zinc (K + -Ca ++ -Zn ++ -CMC), (vi) carboxymethyl cellulose potassium calcium magnesium (K + -Ca ++ -Mg ++ -CMC), (vii) carboxymethyl cellulose potassium calcium tin (K + -Ca ++ -Sn ++ -CMC), (viii) carboxymethyl cellulose potassium magnesium zinc (K + -Mg ++ -Zn ++ -CMC), (ix) carboxymethyl cellulose potassium magnesium tin (K +-Mg ++ -Sn ++ -CMC) and (x) carboxymethyl cellulose potassium zinc tin (K + -Zn ++ -Sn ++ -CMC).
[0060] In another non-limiting embodiment, the functionalized water-soluble carboxymethyl cellulose is selected from the group consisting of: (i) lithium calcium carboxymethyl cellulose (Li + -Ca ++ -CMC), (ii) lithium magnesium carboxymethyl cellulose (Li + -Mg ++ -CMC), (iii) carboxymethyl cellulose lithium zinc (Li + -Zn ++ -CMC), (iv) carboxymethyl cellulose lithium tin (Li + -Sn ++ -CMC), (v) carboxymethyl cellulose lithium calcium zinc (Li + -Ca ++ -Zn ++ -CMC), (vi) lithium calcium magnesium carboxymethyl cellulose (Li + -Ca ++ -Mg ++ -CMC), (vii) carboxymethyl cellulose lithium calcium tin (Li + -Ca ++ -Sn ++ -CMC), (viii) carboxymethyl cellulose lithium magnesium zinc (Li + -Mg ++ -Zn ++ -CMC), (ix) carboxymethyl cellulose lithium magnesium tin (Li + -Mg ++ -Sn ++ -CMC) and (x) carboxymethyl cellulose lithium zinc tin (Li + -Zn ++ -Sn ++ -CMC).
[0061] In another non-limiting embodiment, the functionalized CMC is sodium calcium carboxymethyl cellulose (Na + -Ca ++ -CMC) or sodium magnesium carboxymethyl cellulose (Na + -Mg ++ -CMC) or sodium zinc carboxymethyl cellulose (Na + -Zn ++ -CMC).
[0062] In another non-limiting embodiment, the functionalized carboxymethyl cellulose (CMC) is a combination of: (i) sodium carboxymethyl cellulose (Na + -CMC), (ii) (a) sodium carboxymethyl cellulose calcium (Na + -Ca ++ -CMC) or (b) sodium magnesium carboxymethyl cellulose (Na + -Mg ++ -CMC) or (c) sodium zinc carboxymethyl cellulose (Na + -Zn ++ -CMC).
[0063] The functionalized carboxymethyl cellulose is in the form of microcrystals, particles, powder or solution.
[0064] In another non-limiting embodiment, the functionalized carboxymethyl cellulose (CMC) is used in oral care compositions, pharmaceutical compositions, home care compositions, industrial compositions, skin care compositions, food and nutraceutical compositions, coating compositions, and oil & energy compositions.
[0065] The functionalized carboxymethyl cellulose (CMC) is used in an oral care composition selected from a mucoadhesive composition, a toothpaste / dentifogrum composition, an oral treatment composition, a mouthwash composition, and a denture adhesive composition.
[0066] In another non-limiting embodiment, the present application provides a mucoadhesive composition comprising: (i) (a) 0.1 wt % to 60 wt % of at least one monovalent (M + ) cation and at least one divalent (M ++ ) a water-soluble salt of a cationically functionalized carboxymethyl cellulose (CMC), or (b) 0.1 wt % to 60 wt % of (b1) composed of a monovalent (M + ) cation and at least one divalent (M ++ ) a water-soluble salt of a cationically functionalized carboxymethyl cellulose (CMC) and (b2) at least one monovalent (M + ) a water-soluble salt of a cationically functionalized carboxymethyl cellulose (CMC); (ii) 0.1 wt % to 60 wt % of a maleic acid or maleic anhydride copolymer of a C1 to C4 alkyl vinyl ether and maleic acid or anhydride monomer, the maleic acid or maleic anhydride copolymer being a substantially alternating structure of monomers and 50 wt % to 90 wt % of the acid moieties in the polymer being converted to metal salts or mixed salts; and (iii) 0.1 wt % to 80 wt % of at least one additional ingredient.
[0067] In another embodiment, the present application discloses a mucoadhesive composition comprising a functionalized carboxymethyl cellulose, wherein the amount of the functionalized carboxymethyl cellulose is from about 0.1% to about 1% by weight, or from about 1% to about 2.5% by weight, or from about 2.5% to about 5% by weight, or from about 5% to about 10% by weight, or from about 10% to about 15% by weight, or from about 15% to about 20% by weight, or from about 20% to about 25% by weight, or from about 25% to about 30% by weight, or from about 30% to about 35% by weight, based on the total weight of the composition. %, or about 35 wt % to about 40 wt %, or about 40 wt % to about 45 wt %, or about 45 wt % to about 50 wt %, or about 50 wt % to about 55 wt %, or about 55 wt % to about 60 wt %, or about 60 wt % to about 65 wt %, or about 65 wt % to about 70 wt %, or about 70 wt % to about 75 wt %, or about 75 wt % to about 80 wt %, or about 80 wt % to about 85 wt %, or 85 wt % to about 90 wt %, or 90 wt % to about 95 wt %, or 95 wt % to about 99.9 wt %.
[0068] The mucoadhesive composition comprises a water-soluble functionalized carboxymethyl cellulose (CMC) having a degree of substitution ranging from 0.4 to 1.2. The water-soluble functionalized biodegradable carboxymethyl cellulose (CMC) has a degree of substitution ranging from 0.4 to 0.7.
[0069] The functionalized carboxymethyl cellulose has a weight average molecular weight ranging from 2000 Daltons to 2000,000 Daltons.
[0070] In another non-limiting embodiment, the mucoadhesive composition comprises a maleic acid or maleic anhydride copolymer of a C1 to C4 alkyl vinyl ether and a maleic acid or anhydride monomer, wherein the maleic acid or maleic anhydride copolymer is a substantially alternating structure of monomers and 50 wt % to 90 wt % of the acid moieties in the polymer are converted to at least one monovalent cation (M + ) and at least one divalent cation (M ++ ). Accordingly, the maleic acid or maleic anhydride copolymer comprises maleic acid or maleic anhydride and C1-C4 alkyl vinyl ether, the predetermined weight average molecular weight of the maleic acid or maleic anhydride copolymer is about 500,000 to 3,000,000, and the maleic acid or maleic anhydride copolymer is prepared by the following method: in a solvent process or a solvent-free process, at about 50° C. to 150° C., in the presence of a free radical initiator, copolymerizing about 50 mol percent of maleic acid or maleic anhydride and about 50 mol percent of C1-C4 alkyl vinyl ether to produce a uniform fine powder substantially free of residual maleic anhydride.
[0071] The maleic acid or maleic anhydride and C1-C4 alkyl vinyl ether are methyl vinyl ether-maleic acid copolymers or methyl vinyl ether-maleic anhydride copolymers having a number average molecular weight of about 50,000 to about 500,000, wherein about 50% by weight to about 100% by weight of the carboxyl units in the polymer are converted into a mixture of metal salts selected from the group consisting of calcium, sodium, strontium, zinc, magnesium, iron, boron, aluminum, potassium, vanadium, chromium, manganese, nickel, copper, yttrium, titanium and mixtures thereof. Preferably, the salt of the methyl vinyl ether-maleic acid copolymer or the methyl vinyl ether-maleic anhydride copolymer has a specific viscosity of about 2.5 to 5.0 when measured at 25° C. in the form of a 1% w / v solution in a methyl ethyl ketone (MEK) solution. The methyl vinyl ether-maleic acid copolymer or the methyl vinyl ether-maleic anhydride copolymer or its salt accounts for about 10% by weight to about 66% by weight of the composition. Preferably, the methyl vinyl ether-maleic acid copolymer or the methyl vinyl ether-anhydride copolymer has a weight average molecular weight of about 700,000 to about 3,000,000.
[0072] In another embodiment, the mucoadhesive composition of the present invention provides an additional component selected from the group consisting of abrasives, anti-caking agents, antifungal agents, antimicrobial agents, anesthetics, antioxidants, antibiotics, anti-inflammatory agents, binders, buffers, colorants, cooling agents, dentin desensitizers, dispersants, enzymes, foaming agents, flavors, fillers, fragrances, gelling agents, humectants, hydrophobic carriers, hydrophilic non-oil components, preservatives, pigments, plasticizers, analgesics, sweeteners, thickeners, viscosity modifiers, excipients, surfactants, stabilizers, sensates, and mixtures thereof. Preferably, the additional component is selected from petrolatum, mineral oil, olive oil, vegetable oil, silicone, glycerol, polyethylene glycol, propylene glycol, polypropylene glycol, poly(ethylene oxide-propylene oxide) copolymers, diethylene glycol, triethylene glycol, sorbitol, water, and mixtures thereof.
[0073] In another non-limiting embodiment, the mucoadhesive composition is a buccal composition, an oral composition, a vaginal composition, a nasal composition, a rectal composition, an ophthalmic composition, a sublingual composition, a palatal composition, and a denture adhesive composition. The mucoadhesive composition is formulated as an ointment, a lotion, a liquid, a solid, a semisolid, an emulsion, a powder, a paste, a dispersion, a gel, a patch, an aerosol, or a spray.
[0074] In another non-limiting embodiment, the present application provides a denture adhesive composition comprising: (i) (a) 0.1 wt % to 60 wt % of at least one monovalent (M + ) cation and at least one divalent (M ++) a water-soluble salt of a cationically functionalized carboxymethyl cellulose (CMC), or (b) 0.1 wt % to 60 wt % of (b1) composed of a monovalent (M + ) cation and at least one divalent (M ++ ) a water-soluble salt of a cationically functionalized carboxymethyl cellulose (CMC) and (b2) at least one monovalent (M + ) a water-soluble salt of a cationically functionalized carboxymethyl cellulose (CMC); (ii) 0.1 wt % to 60 wt % of a maleic acid or maleic anhydride copolymer of a C1 to C4 alkyl vinyl ether and a maleic acid or anhydride monomer, the maleic acid or maleic anhydride copolymer being a substantially alternating structure of monomers and 50 wt % to 90 wt % of the acid moieties in the polymer being converted to metal salts or mixed salts; and (iii) 0.1 wt % to 80 wt % of at least one additional ingredient. The denture adhesive composition comprises a water-soluble functionalized carboxymethyl cellulose (CMC) having a degree of substitution ranging from 0.4 to 0.7. Preferably, the denture adhesive composition comprises a water-soluble functionalized carboxymethyl cellulose (CMC) having a degree of substitution ranging from 0.4 to 1.2.
[0075] The functionalized carboxymethyl cellulose has a weight average molecular weight range of 2000 Daltons to 2000,000 Daltons. The maleic acid or maleic anhydride copolymer of C1 to C4 alkyl vinyl ether and maleic acid or anhydride monomer is a mixed sodium and calcium salt of methyl vinyl ether and maleic anhydride, having a specific viscosity of about 2.5 to 5.0 when measured as a 1% w / v solution in methyl ethyl ketone (MEK) solution at 25°C.
[0076] In another non-limiting embodiment, the present application provides a toothpaste composition comprising: (i) (a) 0.1 wt % to 20 wt % of at least one monovalent (M + ) cation and at least one divalent (M ++ ) a water-soluble salt of a cationically functionalized carboxymethyl cellulose (CMC), or (b) 0.1 wt % to 20 wt % of (b1) composed of at least one monovalent (M + ) cation and at least one divalent (M ++ ) a water-soluble salt of a cationically functionalized carboxymethyl cellulose (CMC) and (b2) at least one monovalent (M +) a water-soluble salt of a cationically functionalized carboxymethyl cellulose (CMC); (ii) 0.1 wt % to 60 wt % of an orally acceptable solvent or carrier including, but not limited to, water, glycerol, polyethylene glycol, polypropylene glycol, sorbitol, or a combination thereof, 0.1 wt % to 20 wt % of a polymer of an orally acceptable monomer including, but not limited to, maleic anhydride, maleic acid, C1 to C4 alkyl vinyl ether, alkylene oxides, alkyl lactams, triglycerides, animal or vegetable oils, or a combination thereof; and (iii) 0.1 wt % to 80 wt % of an additional ingredient including, but not limited to, a component selected from the group consisting of calcium carbonate, calcium bicarbonate, silicon dioxide, sodium carbonate, abrasives from the group of sodium bicarbonate and combinations thereof, surfactants selected from the group including anionic surfactants, cationic surfactants, nonionic surfactants, zwitterionic surfactants and combinations thereof, active substances selected from compounds providing fluoride, zinc salts of organic and inorganic acids, flavoring agents, foam enhancers, stabilizers, film-forming polymers, peroxides, rheology modifiers, thickeners, salts, sweeteners, colorants, whitening agents, antimicrobial agents, antiplaque agents, antitartar agents, antibiofilm agents, antisensitivity agents, antigingivitis agents, mouthfeel agents, sealants and compounds, detergents, antifouling agents, vitamins and minerals, humectants, preservatives, dispersants, sedimentation agents, pH adjusters and combinations thereof.
[0077] The one or more oral care active ingredients in the oral care compositions of the present disclosure can be selected from the group consisting of analgesics, antibacterial agents, anti-calculus agents, antibiotics, antioxidants, odor fresheners or breath fresheners, cooling agents, caffeine, medications, desensitizers, tooth remineralizers, enzymes, herbal agents, drugs, minerals, peptides, pharmaceuticals, probiotics, preservatives, sensates, taste masking agents, flavors, therapeutic agents, throat soothing agents, vitamins, warming agents, and mixtures thereof.
[0078] Non-limiting examples of humectants may be or may include glycerin, propylene glycol, and combinations thereof.The toothpaste composition may include one or more whitening agents, not limited to hydrogen peroxide or one or more sources of hydrogen peroxide.
[0079] Non-limiting examples of antimicrobial agents may include zinc ion sources such as zinc acetate, zinc citrate, zinc gluconate, zinc glycinate, zinc oxide, zinc sulfate, and sodium zinc citrate; phthalic acid and its salts such as magnesium monopotassium phthalate; hexetidine; octenidine; sanguinarine; benzalkonium chloride; domiphene bromide; bromide); alkyl pyridinium chlorides, such as hexadecyl pyridinium chloride (CPC) (including combinations of CPC with zinc and / or enzymes), tetradecyl pyridinium chloride and N-tetradecyl-4-ethyl pyridinium chloride; iodine; sulfonamides, biguanides, such as alexidine, chlorhexidine; digluconates; piperidino derivatives, such as delmopinol and octapinol, magnolia extract, grape seed extract, raspberry ketone, menthol, geraniol, citral , eucalyptol, eugenol, stannous fluoride, monosodium magnolia bark extract, Chinese medicine, thymol, 4-isopropyl metacresol (IPMP, o-tolyl-5-ol); antibiotics, such as amoxicillin, tetracycline, doxycycline, minocycline, metronidazole, neomycin, kanamycin and clindamycin, etc. A further illustrative list of useful antibacterial agents is provided in US Patent No. 5,776,435 issued to Gaffar et al.
[0080] Non-limiting examples of antimicrobial agents include: halogenated diphenyl ethers, 2,4,4-trichloro-2'-hydroxy-diphenyl ether, 2,2-dihydroxy-5,5-dibromo-diphenyl ether, 2,2-methylenebis-4(4-chloro-6-bromo-phenol), halogenated salicylanilides and halogenated cabanilides, stannous chloride, zinc lactate, zinc citrate, zinc oxide.
[0081] The limiting examples of flavoring agent include those flavoring agents known to the technician, such as natural flavoring agents and artificial flavoring agents. These flavoring agents are selected from synthetic flavoring oils, flavoring aromatics and / or flavoring oils, oleoresins and extracts and combinations thereof obtained from plants, leaves, flowers, fruits, etc. Non-restrictive representative flavoring oils include spearmint oil, cinnamon oil, wintergreen oil (methyl salicylate), peppermint oil, clove oil, bay oil, anise oil, eucalyptus oil, thyme oil, cedar leaf oil, nutmeg oil, allspice (allspice), sage oil, nutmeg oil, bitter almond oil and cassia oil. In addition, useful flavoring agents are artificial fruit flavoring agents, natural fruit flavoring agents and synthetic fruit flavoring agents, such as vanilla oil and citrus oils include lemon, orange, lime, grapefruit and fruit flavoring agents include apple, pear, peach, grape, blueberry, strawberry, raspberry, cherry, plum, pineapple, apricot, etc. These flavoring agents can be used in liquid form or solid form, and can be used alone or in combination. Commonly used flavoring agents include mints such as peppermint, menthol, spearmint, artificial vanilla, cinnamon derivatives and various fruit flavorings, either alone or in admixture.
[0082] When used in combination with a cooling agent, flavoring agents can also provide breath freshening properties, particularly minty flavor. Other useful flavoring agents include aldehydes, esters and ketones, such as cinnamyl acetate, cinnamaldehyde, lemon diethyl acetal, dihydrocarvyl acetate, eugenol formate, raspberry ketone, p-methylaminophenol (p-methyl-amisol) etc. Generally, any flavoring agent or food additive can be used, such as those described in "Chemicals Used in Food Processing" on pages 63-258 of No. 1274 publications published by the National Academy of Sciences of the United States. This publication is incorporated herein by reference. It can include natural flavoring agents and synthetic flavoring agents.
[0083] Non-limiting examples of suitable animal and vegetable oils may include, but are not limited to, sunflower oil, corn oil, soybean oil, avocado oil, jojoba oil, pumpkin oil, raisin seed oil, sesame seed oil, walnut oil, fish oil, glycerol tricaprocaprylate, Purcell oil, liquid jojoba oil, and blends thereof. Natural oils are also suitable, such as eucalyptus oil, lavender oil, vetiver oil, litsea cubeba oil, lemon oil, sandalwood oil, rosemary oil, chamomile oil, savory oil, nutmeg oil, cinnamon oil, hyssop oil, coriander oil, orange oil, geranium oil, juniper oil, bergamot oil, and blends thereof. There are five commonly available vegetable oils containing more than 50% linoleic acid groups (as their glycerides). In descending order of linolenic acid content: safflower oil (75%), sunflower oil (67.8%), corn oil (56%), cottonseed oil (55%), and soybean oil (52%).
[0084] Non-limiting examples of suitable vitamins or minerals can include vitamin A, vitamin C, vitamin D, vitamin E, vitamin K, vitamin B6, vitamin B12, thiamine, riboflavin, biotin, folic acid, niacin, pantothenic acid, sodium, potassium, calcium, magnesium, iron, copper, zinc, selenium, manganese, choline, chromium, molybdenum, cobalt, and combinations thereof.
[0085] Similarly, non-limiting examples of whitening agents that can be used in the oral care compositions of the present invention include, but are not limited to, dyes, polyphosphates, phytic acid and its salts, complex bleaching agents or bleaching agents. Suitable bleaching agents or whitening agents include peracids, peroxide compounds. Peroxides are believed to whiten teeth by releasing hydroxyl radicals that can break down the plaque-stain complex into a form that can be washed away or removed by abrasives.
[0086] In addition, film-forming polymers may be included in the oral care composition of the present invention. Suitable examples of such film-forming polymers may include, but are not limited to, synthetic anionic polymerized polycarboxylic acid (SAPP), such as PVM / MA copolymers (Gantrez S-97, Ashland Inc.). Such polymers are also described in US Patent Nos. 5,334,375 and 5,505,933. SAPP has been described as being useful for reducing dentin sensitivity. In addition, SAPP has been described as an antibacterial enhancer that increases the delivery of antibacterial agents to oral surfaces and increases the retention of antibacterial agents on oral surfaces. Within the contemplation of the present invention, film-forming polymers such as PVM / MA copolymers may be used in the compositions of the present invention as a means to reduce stain formation.
[0087] Non-limiting examples of sweeteners may include, but are not limited to, sucrose, glucose, saccharin, dextrose, levulose, lactose, mannitol, sorbitol, fructose, maltose, xylitol, erythritol, saccharin salts, thaumatin, aspartame, D-tryptophan, dihydrochalcone, acesulfame potassium, sucralose, and sodium cyclamate, particularly sodium cyclamate and sodium saccharin, and mixtures thereof.
[0088] The oral care composition according to the present disclosure may also include an abrasive. Suitable and non-limiting examples of such abrasives may include silica abrasives, such as standard cleaning silica, high cleaning silica, or any other suitable abrasive silica. In addition to or in place of silica abrasives, further examples of abrasives that may be used include, for example, calcium phosphate abrasives, such as tricalcium phosphate (Ca3(PO4)2), hydroxyapatite (Ca 10(PO4)6(OH)2) or dicalcium phosphate dihydrate CaHPO4.2H2O or calcium pyrophosphate; calcium carbonate abrasive; or abrasives such as, for example, sodium metaphosphate, potassium metaphosphate, aluminum silicate, calcined alumina, bentonite or other siliceous materials or combinations thereof. The silica component of the silica substrate of the present invention is amorphous precipitated silica. Precipitated silica includes the following products available from JM Huber Corporation, Edison, NJ:
[0089]
[0090]
[0091] Oral care compositions according to the present disclosure can also include suitable anionic surfactants. Suitable examples of such surfactants can include, but are not limited to, water-soluble salts of alkyl sulfates (such as sodium alkyl sulfate) with 8 to 20 carbon atoms in the alkyl free radical and water-soluble salts of sulfonated monoglycerides of fatty acids with 8 to 20 carbon atoms, such as sodium lauryl sulfate and sodium coconut oil monoglyceride sulfonate. Other suitable anionic surfactants are sarcosinates such as sodium lauroyl sarcosinate, taurates, sodium lauryl sulfoacetate, sodium lauroyl isethionate, sodium lauryl carboxylate, sodium dodecylbenzene sulfonate and mixtures thereof. Other useful anionic surfactants include sarcosinate surfactants, isethionate surfactants and taurate surfactants. Surfactants are alkali metal salts or ammonium salts of these surfactants, lauroyl sarcosine, myristoyl sarcosine, palmitoyl sarcosine, stearoyl sarcosine, Amisoft CS-11 (amino acid and L-glutamic acid) and sodium and potassium salts of oleoyl sarcosine.
[0092] Examples of suitable cationic surfactants are derivatives of fatty quaternary ammonium compounds having a long alkyl chain containing about 8 to 18 carbon atoms, such as lauryltrimethylammonium chloride, cetylpyridinium chloride, cetyltrimethylammonium bromide, diisobutylphenoxyethyldimethylbenzylammonium chloride, cocoalkyltrimethylammonium nitrate, cetylpyridinium fluoride, and the like.
[0093] Examples of suitable nonionic surfactants can include, but are not limited to, Pluronics, polyethylene oxide condensates of alkylphenols, products derived from the condensation of ethylene oxide with the reaction products of propylene oxide and ethylenediamine, ethylene oxide condensates of fatty alcohols, long chain tertiary amine oxides, long chain tertiary phosphine oxides, long chain dialkyl sulfoxides, and mixtures of such materials.
[0094] Examples of suitable zwitterionic surfactants can include, but are not limited to, derivatives of fatty quaternary ammonium compounds, fatty quaternary phosphonium compounds, and fatty quaternary sulfonium compounds, wherein the fatty radical can be straight chain or branched, and wherein one of the fatty substituents contains about 8 to 18 carbon atoms and one contains an anionic water-solubilizing group, such as carboxyl, sulfonate, sulfate, phosphate, or phosphonate.
[0095] In another embodiment of the present disclosure, the oral care composition can also include a rheology modifier. Suitable examples of such thickeners include, but are not limited to, water-soluble cellulose ethers, such as sodium carboxymethylcellulose, sodium carboxymethyl hydroxyethylcellulose and hydroxyethylcellulose, vinyl pyrrolidone polymers (also referred to as N-vinyl pyrrolidone, N-vinyl-2-pyrrolidone, N-vinyl-2-pyrrolidone and polyvinyl pyrrolidone) as monomer units. Other suitable thickeners include carboxyvinyl polymers (carbomer), carrageenan, laponite and other natural gums, such as karaya gum, xanthan gum, guar gum, gum arabic and tragacanth. Colloidal magnesium aluminum silicate or finely divided silicon dioxide can be used as a part of thickener, to further improve texture. A class of other thickeners or gelling agents include a class of acrylic acid homopolymers cross-linked with the alkyl ethers of pentaerythritol or the alkyl ethers of sucrose. In a plurality of preferred embodiments, the carrier may comprise a polymer and / or copolymer of polyethylene glycol, a polymer and / or copolymer of ethylene oxide / propylene oxide, and a polymer and / or copolymer of silicone. If such copolymers / polymers are used, they may be selected from commercially available materials. Block copolymers of ethylene oxide and propylene oxide are useful, but preferably higher molecular weight, e.g., >5000 Da, e.g., including PLURACARE (R) L1220 (available from BASF, Wyandotte, Mich., U.S.). Low molecular weight or medium molecular weight polyethylene glycols such as PEG400, PEG 600, PEG 800, PEG 1000 and mixtures thereof are also useful. Preferably, the carrier provides a tooth powder having a viscosity of about 10,000 CPS to about 700,000 CPS, preferably about 30,000 CPS to about 300,000 CPS.
[0096] Non-limiting examples of "fluoride-providing compounds" can include sodium fluoride, potassium fluoride, amine fluorides, ammonium fluoride, lead fluoride, manganese fluoride, copper fluorides such as cuprous fluoride, zinc fluoride, barium fluoride, sodium fluorosilicate, ammonium fluorosilicate, sodium fluorozirconate, sodium monofluorophosphate, potassium fluorozirconate, sodium monofluorophosphate, aluminum monofluorophosphate and aluminum difluorophosphate, sodium calcium pyrophosphate fluoride, tin fluorides such as stannous fluoride, tin fluoride or stannous fluorochloride, and sodium hexafluorostannate.
[0097] Accordingly, the toothpaste composition is an aqueous composition or an anhydrous composition.
[0098] In another non-limiting embodiment, the present application discloses a method for preparing functionalized carboxymethyl cellulose, the method comprising an ion exchange process, the ion exchange process comprising (i) at least one monovalent (M + ) carboxymethyl cellulose salt and (ii) one or more divalent (M ++ ) metal salt reaction; wherein the divalent (M ++ ) Salt is selected from M ++ Chloride or M ++ Sulfate or M ++ The carbonate group, wherein the final functionalized CMC polymer M + With M ++ The weight ratio is from about 1:75 to about 75:1.
[0099] In another non-limiting embodiment, the present application provides a method for preparing a monovalent-divalent (M + -M ++ ) a method for preparing carboxymethyl cellulose, the method comprising: (i) preparing (a) M ++ Chloride, M ++ Sulfate or M ++ carbonate and (b) an aqueous solution of a C2-C4 alcohol; (ii) adding sodium carboxymethyl cellulose (M + ), and stirring the resultant at ambient temperature for at least 30 minutes; (iii) filtering the resultant of step (ii) to obtain a wet cake; (iv) stirring the wet cake of step (iii) in a hydroalcoholic solution for at least 30 minutes; (v) repeating step (iv) at least 3 times to obtain pure M + -M ++ - a wet cake of carboxymethyl cellulose; (vi) drying the wet cake of step (v) in a fluidized bed dryer at 50°C to 70°C for at least 15 minutes to 30 minutes to obtain a dry M + -M ++ - carboxymethyl cellulose; and (vii) grinding the resultant of step (vi) to separate M + -M ++ -Dry powder of carboxymethyl cellulose.
[0100] The M + -M ++ The carboxymethyl cellulose is sodium calcium carboxymethyl cellulose. ++ Chloride, M ++ Sulfate or M ++The carbonate is calcium chloride, calcium sulfate or calcium carbonate. The C1-C4 alcohol is selected from methanol, ethanol, propanol, isopropanol and butanol. The powder is ground in a mill using 0.75 mm, 0.20 mm and 0.08 mm screens. The average particle size of the dry powder ranges from 20 microns to 300 microns.
[0101] Therefore, the functionalized carboxymethyl cellulose of the present invention has a number of unique features, namely: (i) having multivalent cations and at least one divalent (M ++ ) cations (e.g., calcium, magnesium, zinc, and tin); (ii) have a low to medium molecular weight (2000 Daltons to 200,000 Daltons) or a medium to high molecular weight (200,000 Daltons to 2,000,000 Daltons); (iii) are very soluble in water; and (iv) are biodegradable, making them suitable for use in the preparation of mucoadhesive compositions, including use in denture adhesives and toothpaste formulations.
[0102] In addition, certain aspects of the present application are illustrated in detail by the following examples.Therefore, each example provided herein must be interpreted as merely illustrative, and not limiting the scope of the present invention in any way.
[0103] Example
[0104] The following examples illustrate the manufacture and use of functionalized carboxymethyl cellulose and a process and method for producing a mucoadhesive composition comprising at least one monovalent (M + ) cation and at least one divalent (M ++ ) compositions of high molecular weight carboxymethyl cellulose that are cationically functionalized.
[0105] Example 1: Prototype Na + -Ca ++ -Synthesis of CMC polymer XA-1517-050-1
[0106] Dissolve 4.35 g of anhydrous calcium chloride in 320 g of deionized water and stir for 30 minutes. Add 1,280 g of methanol while stirring. Add 128 g of Aqualon supplied by Ashland Specialty Ingredients while stirring. TM CMC 7H3SXF grade carboxymethyl cellulose was added to the solution to form a heterogeneous slurry. The mixture was stirred for 20 hours and then filtered to obtain a wet cake. The wet cake was dispersed in 1,600 grams of 80 / 20 w / w methanol / water, stirred for 30 minutes, and then filtered again. This step was repeated two more times, followed by a final wash in 1,600 grams of pure methanol. The final material was dried using a fluidized bed dryer at 65°C until the total moisture content of the final product was less than 5% by weight.
[0107] Example 2: Prototype Na + -Ca ++ -Synthesis of CMC polymer XA-1517-050-2
[0108] Dissolve 13.40 grams of anhydrous calcium chloride in 320 grams of deionized water and stir for 30 minutes. Add 1,280 grams of methanol while stirring continuously. Add 128 grams of Aqualon supplied by Ashland Specialty Ingredients while stirring continuously. TM CMC 7H3SXF grade carboxymethyl cellulose was added to the solution to form a heterogeneous slurry. The mixture was stirred for 20 hours and then filtered to obtain a wet cake. The wet cake was dispersed in 1,600 grams of 80 / 20 w / w methanol / water, stirred for 30 minutes, and then filtered again. This step was repeated two more times, followed by a final wash in 1,600 grams of pure methanol. The final material was dried using a fluidized bed dryer at 65°C until the total moisture content of the final product was less than 5% by weight.
[0109] Example 3: Prototype Na + -Ca ++ -Synthesis of CMC polymer XA-1517-078
[0110] Dissolve 120.00 grams of anhydrous calcium chloride in 800 grams of deionized water and stir for 30 minutes. Add 800 grams of isopropanol while stirring. Add 180 grams of Aqualon supplied by Ashland Specialty Ingredients while stirring. TM CMC 7H3SXF grade carboxymethyl cellulose was added to the solution to form a heterogeneous slurry. The mixture was stirred for 20 hours and then filtered to obtain a wet cake. The wet cake was dispersed in 1,600 grams of 80 / 20 w / w methanol / water, stirred for 30 minutes, and then filtered again. This step was repeated two more times, followed by a final wash in 1,600 grams of pure methanol. The final material was dried using a fluidized bed dryer at 65°C until the total moisture content of the final product was less than 5% by weight.
[0111]
[0112] Table 1:Na + -Ca ++ - Characteristic properties of CMC polymer prototypes
[0113] Example 4: Prototype Na + -Mg ++ -Synthesis of CMC polymer (XA1517-018)
[0114] 63.0 grams of cellulose (42.00 grams of Gaomi 2600 and 21.00 grams of NB421) were combined with 711.84 grams of isopropanol, 21.00 grams of deionized water, and 21.86 grams of magnesium chloride hexahydrate in a 1.5 liter stainless steel reactor. The reactor was sealed, stirring was started using an overhead impeller, the reactor was cooled to 20°C, and the oxygen in the reactor was purged by 3 vacuum / ultrapure nitrogen backfills. Then, 95.39 grams of a 50% solution of NaOH in deionized water was added, followed by two more inert / ultrapure nitrogen backfills. The mixture was stirred at 20°C for 1 hour, and then 88.90 grams of a 50% solution of monochloroacetic acid in isopropanol was added. The reactor was then heated to 70°C over 30 minutes, maintained at 70°C for 75 minutes, and cooled to 30°C over 30 minutes. The final material was then removed from the reactor, filtered, and the resulting wet cake was washed in 800 g of 80 / 20 w / w methanol / water for 30 minutes and neutralized to pH 7 using concentrated hydrochloric acid. The slurry was then filtered and the resulting wet cake was subjected to another washing and neutralization step. A third wash was performed in the same solvent system, this time without neutralization, and a final wash was performed in 800 g of pure methanol. The final material was dried at 65° C. using a fluidized bed dryer until the total moisture content of the final product was less than 5% by weight. The resulting dry material was ground to the desired particle size using a Retsch mill.
[0115] Example 5: Prototype Na + -Mg ++ -Synthesis of CMC polymer (XA1517-020)
[0116] 63.0 grams of cellulose (42.00 grams of Gaomi 2600 and 21.00 grams of NB421) were combined with 711.84 grams of isopropanol and 49.68 grams of magnesium chloride hexahydrate in a 1.5 liter stainless steel reactor. The reactor was sealed, stirring was started using an overhead impeller, the reactor was cooled to 20°C, and the oxygen in the reactor was purged by 3 vacuum / ultrapure nitrogen backfills. Then, 117.28 grams of a 50% solution of NaOH in deionized water was added, followed by two more inert / ultrapure nitrogen backfills. The mixture was stirred at 20°C for 1 hour, and then 88.90 grams of a 50% solution of monochloroacetic acid in isopropanol was added. The reactor was then heated to 70°C over a period of 30 minutes, maintained at 70°C for 75 minutes, and cooled to 30°C over a period of 30 minutes. The final material was then removed from the reactor, filtered, and the resulting wet cake was washed in 800 g of 80 / 20 w / w methanol / water for 30 minutes and neutralized to pH 7 using concentrated hydrochloric acid. The slurry was then filtered and the resulting wet cake was subjected to another washing and neutralization step. A third wash was performed in the same solvent system, this time without neutralization, and a final wash was performed in 800 g of pure methanol. The final material was dried at 65° C. using a fluidized bed dryer until the total moisture content of the final product was less than 5% by weight. The resulting dry material was ground to the desired particle size using a Retsch mill.
[0117] Table 2: Na + -Mg ++ - Characteristic properties of CMC polymer prototypes
[0118]
[0119] DS-degree of substitution (CmDs); MW-molecular weight (Dalton),
[0120] Viscosity (cPs) (1% in water), pH (@1% aqueous solution)
[0121] Example 6: Prototype Na + -Zn ++ -Synthesis of CMC polymer (XA-1532-005)
[0122] Dissolve 73.00 grams of anhydrous zinc chloride in 752.17 grams of deionized water and stir for 30 minutes. Add 758.09 grams of isopropanol while stirring. Add 120 grams of Aqualon supplied by Ashland Specialty Ingredients while stirring. TM CMC 7H3SXF grade carboxymethyl cellulose (XA1517-041, Table 1) is added to the solution to form a heterogeneous slurry. The mixture is stirred for 20 hours and then filtered to obtain a wet cake. The wet cake is dispersed in 1025 grams of 70 / 30w / w methanol / water, stirred for 30 minutes, and then filtered again. This step is repeated twice, and then washed for the last time in 1025 grams of pure methanol. The final material is dried at 65°C using a fluidized bed dryer until the total moisture content of the final product is less than 5% by weight. Important polymer properties are shown in Table 3.
[0123] Example 7: Prototype Na + -Zn ++ -Synthesis of CMC polymer (XA1532-068)
[0124] Dissolve 35.30 g of anhydrous zinc chloride in 681.36 g of deionized water and stir for 30 minutes. Add 2779.66 g of methanol while stirring continuously. Add 275.00 g of Aqualon supplied by Ashland Specialty Ingredients while stirring continuously. TM CMC 7H3SXF grade carboxymethyl cellulose (XA1517-041, Table 1) was added to the solution to form a heterogeneous slurry. The mixture was stirred for 20 hours and then filtered to obtain a wet cake. The wet cake was dispersed in 2,350 grams of 70 / 30w / w methanol / water, stirred for 30 minutes, and then filtered again. This step was repeated twice and then washed for the last time in 2,350 grams of pure methanol. The final material was dried at 65°C using a fluidized bed dryer until the total moisture content of the final product was less than 5% by weight. Important polymer properties are shown in Table 3.
[0125] Table 3: Na +-Zn ++ - Characteristic properties of CMC polymer prototypes
[0126]
[0127] DS-degree of substitution (CmDs); MW-molecular weight (Daltons)
[0128] Viscosity (1% in water) (cPs), pH (@1% aqueous solution)
[0129] Example 8: Preparation of denture adhesive formulation
[0130] A general method for preparing a standard denture adhesive paste is described herein. The ingredients and their amounts used in the preparation of various denture adhesive formulations are described in Tables 4, 5, and 6. Denture adhesive pastes were prepared in 25 gram batches. The required amounts of petrolatum and mineral oil were placed in a 100 mL plastic jar equipped with a screw cap, and the petrolatum and mineral oil were melted by immersing the plastic jar in a water bath maintained at 70°C to 80°C and mixing thoroughly until a transparent homogeneous liquid was obtained. First, the solid CMC polymer component was added to the molten oil mixture in the amounts shown in Tables 4, 5, and 6, gently folded in, and then manually mixed to homogenize. Then, a mixed Ca / Na salt of poly(methyl vinyl ether / maleic acid) - poly(MVE / MA) - (Gantrez TM MS-955, Ashland LLC.) was added to the formulation according to the amount shown in Table 4, Table 5, and Table 6, gently stirred, and then manually mixed to homogenize. The solid polymer was stirred in and manually blended with the oil mixture to obtain a smooth paste, while the plastic jar was immersed in a suitable temperature-controlled water bath to maintain the temperature of the mixture at 70° C. to 80° C. Finally, the denture adhesive paste was subjected to high-speed bladeless centrifugal mixing in a high-speed mixer DAC 400FVZ equipment from FlackTec Inc, Landrum, SC.
[0131] Table 4: Na content + -Mg ++ -CMC denture adhesive preparation
[0132]
[0133] Table 5: Na content + -Ca ++ -CMC denture adhesive preparation
[0134]
[0135] Table 6: Na content + -Zn ++ -CMC denture adhesive preparation
[0136]
[0137] Example 9: In vitro denture adhesive test method
[0138] Adhesion force and relative denture adhesive film thickness were recorded on a TA.XT Plus texture analyzer from StableMicrosystems Texture Technologies Corp. equipped with a 50 Kg load cell and connected to a PC running Exponent software version 6.1.11.0. The texture analyzer was equipped with a custom-made denture-shaped plexiglass probe fixture assembly. Injection of artificial saliva between the walls of the plexiglass probe fixture assembly was achieved using a peristaltic pump. Real-time time-lapse images of denture adhesive pastes evaluated for adhesion performance on the texture analyzer were recorded using a Canon EOS 5dMark IV digital SLR camera.
[0139] Before each test, the prepared denture adhesive formulation was manually mixed to a homogenous and uniform paste consistency. Three almost identical strips of denture adhesive paste were weighed on an analytical balance and placed in the denture-shaped cavity of the bottom plexiglass fixture. At each test, the total mass of the denture adhesive paste applied to the bottom fixture was 2.0 (+ 0.1) g. The bottom fixture was mounted on a texture analyzer, and the top probe was moved down into the cavity of the bottom fixture to evenly disperse the denture adhesive paste and fill the lower half of the cavity under a precise compression force of 4.5 Kg. Artificial saliva was injected. Throughout the experiment, the denture adhesive paste remained in contact and immersed in a thin level of artificial saliva that was continuously updated at a flow rate of 1 mL / min. Once the denture adhesive paste layer was completely covered with artificial saliva, a 7-hour series of tests began. The adhesion force (in Newtons) during chewing and the thickness (in mm) of the denture adhesive film between the upper and lower probes were continuously measured during the experiment. Four rounds of continuous experiments were performed on each sample of the prepared denture adhesive formulation. The average plot of the four runs for each sample was compared for adhesion performance and thickness variation. The total adhesion for each sample was calculated as the area under the curve of the average plot of four consecutive runs for each sample.
[0140] Example 10: In vitro adhesion results
[0141] Figure 1 The control denture adhesive and Na-containing + -Mg ++- Overlay of average adhesion spectra of denture adhesive formulations (DA29 to DA31) with -CMC. The adhesion spectrum trace for each denture adhesive sample is the average of four consecutive runs. Each overlay is divided into alternating phases of slow chewing motion or rest period (RP) and fast chewing motion or dynamic chewing (DM). Adhesion force is recorded and reported in Newtons (N). Figure 2 The total adhesion of each representative denture adhesive formulation (control, DA29 to DA31) is shown. The total adhesion (in N) was measured as the total area under the curve of the mean adhesion profile trace for each representative denture adhesive formulation.
[0142] Figure 3 , Figure 5 and Figure 7 The control denture adhesive and Na-containing + -Ca ++ - Overlay of average adhesion spectra of denture adhesive formulations (DA35 to DA46) with -CMC. The adhesion spectrum trace for each denture adhesive sample is the average of four consecutive runs. Each overlay is divided into alternating phases of slow chewing motion or rest period (RP) and fast chewing motion or dynamic chewing (DM). The adhesion force is recorded and reported in Newtons (N). Figure 4 , Figure 6 and Figure 8 The total adhesion of each representative denture adhesive formulation (control, DA35 to DA46) is shown. The total adhesion (in N) was measured as the total area under the curve of the average adhesion profile trace for each representative denture adhesive formulation.
[0143] Figures 9 and 11 show the control denture adhesive and Na-containing + -Zn ++ -CMC denture adhesive formulations (DA87 to DA102) are overlaid with average adhesion spectra. The adhesion spectrum trajectory of each denture adhesive sample is the average of four consecutive experiments. Each overlay is divided into alternating phases of slow chewing movement or rest period (RP) and fast chewing movement or dynamic chewing (DM). Adhesion force is recorded and reported in Newtons (N). Figures 10 and 12 show the total adhesion of each representative denture adhesive formulation (control, DA87 to DA102). Total adhesion (in N) is measured as the total area under the curve of the average adhesion spectrum trajectory of each representative denture adhesive formulation. The total adhesion produced by each prototype denture adhesive formulation tested by the in vitro method is shown in Table 7.
[0144] Table 7: Overall adhesion of denture adhesives by in vitro test methods
[0145]
[0146] DA-Denture Adhesive
[0147] Example 11: Containing silicon dioxide and Na + -Zn ++ -CMC toothpaste formula
[0148] A suitably sized vessel was charged with glycerol (1 wt % to 30 wt %) and the divalent cation functionalized Na + -Zn ++ -CMC (0.1 wt % to 6 wt %) is completely dispersed in glycerol. A 70% solution of sorbitol (1 wt % to 30 wt %) is then charged to the same container and mixed thoroughly with an overhead stirrer. Deionized water (1 wt % to 40 wt %) is then added to the container and mixed thoroughly with an overhead stirrer until a homogeneous viscous gel phase is obtained. A previously prepared aqueous solution of sodium fluoride (0.1 wt % to 0.3 wt %) and sodium saccharin (0.1 wt % to 0.5 wt %) is added to the container and mixed thoroughly until homogeneous. The gel phase is transferred to a suitably sized receiving tank of a whipping mixer and the abrasive silica Zeodent 113 (1 wt % to 20 wt %) and thickener silica are added. The mixture is then mixed with a whisk mixer at high speed under vacuum until a uniform paste is obtained. Finally, sodium lauryl sulfate surfactant (0.1% to 5% by weight) and flavoring (0.1% to 5% by weight) are added to the paste and a final round of high speed mixing is performed in a whisk mixer under vacuum to obtain a complete toothpaste formulation.
[0149] Example 12: Containing calcium carbonate and Na + -Zn ++ -CMC toothpaste formula
[0150] A 70% sorbitol (1 wt % to 30 wt %) solution was placed in a suitably sized container and the divalent cation functionalized Na + -Zn ++ -CMC (0.1 wt % to 6 wt %) is completely dispersed in the sorbitol solution. Deionized water (1 wt % to 40 wt %) is then added to the container and mixed thoroughly with an overhead stirrer until a homogeneous viscous gel phase is obtained. A previously prepared aqueous solution of sodium monofluorophosphate (0.1 wt % to 2 wt %), sodium phosphate tribasic decahydrate aqueous solution (0.1 wt % to 2 wt %) and sodium saccharin (0.1 wt % to 0.5 wt %) is added to the container and mixed thoroughly until homogeneous. The gel phase is transferred to a receiving tank of a whipping mixer of suitable size and abrasive calcium carbonate (1 wt % to 50 wt %) and thickener silica are added. The mixture is then mixed with a whisk mixer at high speed under vacuum until a uniform paste is obtained. Finally, sodium lauryl sulfate surfactant (0.1% to 5% by weight) and flavoring (0.1% to 5% by weight) are added to the paste and a final round of high speed mixing is performed in a whisk mixer under vacuum to obtain a complete toothpaste formulation.
[0151] The above description fully discloses the present invention including preferred embodiments thereof. Modifications and improvements to the embodiments specifically disclosed herein are within the scope of the following claims. Without further elaboration, it is believed that one skilled in the art can utilize the present invention to the greatest extent possible in light of the above description. Embodiments of the present invention for which an exclusive right or privilege is claimed are defined as follows.
Claims
1. A method comprising at least one unit price (M + ) cation and at least one divalent (M ++ ) Water-soluble salts of cationically functionalized carboxylated polysaccharides.
2. The composition of claim 1, wherein the functionalized carboxylated polysaccharide is selected from the group consisting of carboxymethyl cellulose, carboxymethyl inulin, carboxymethyl guar gum and carboxymethyl starch.
3. The composition of claim 1, wherein the functionalized carboxylated polysaccharide is carboxymethylcellulose.
4. A method comprising at least one unit price (M + ) cation and at least one divalent (M ++ ) A water-soluble salt of cationically functionalized carboxymethyl cellulose (CMC).
5. The water-soluble salt of carboxymethylcellulose (CMC) according to claim 4, wherein the amount of divalent cation is about 0.2 wt% to 7.5 wt% of the total CMC.
6. The water-soluble salt of carboxymethyl cellulose (CMC) according to claim 4, wherein In the final functionalized CMC polymer, the weight ratio of monovalent cations to divalent cations is 75:1 to 1:
75.
7. The water-soluble salt of carboxymethyl cellulose (CMC) according to claim 4, wherein the carboxymethyl cellulose (CMC) is optionally further mixed with at least one monovalent (M + ) Cationic functionalized carboxymethyl cellulose (CMC) combination.
8. The water-soluble salt of carboxymethyl cellulose (CMC) according to claim 4, wherein the degree of substitution of the functionalized carboxymethyl cellulose (CMC) ranges from 0.4 to 1.
2.
9. The water-soluble salt of carboxymethyl cellulose (CMC) according to claim 4, wherein the degree of substitution of the functionalized carboxymethyl cellulose (CMC) ranges from 0.4 to 0.
7.
10. The water-soluble salt of carboxymethyl cellulose (CMC) according to claim 4, wherein the weight average molecular weight of the functionalized carboxymethyl cellulose ranges from 2000 Daltons to 2000,000 Daltons.
11. The water-soluble salt of carboxymethyl cellulose (CMC) according to claim 4, wherein the weight average molecular weight of the functionalized carboxymethyl cellulose ranges from 80,000 Daltons to 1,300,000 Daltons.
12. The water-soluble salt of carboxymethyl cellulose (CMC) according to claim 4, wherein the functionalized carboxymethyl cellulose (CMC) retains inherent biodegradable properties.
13. The water-soluble salt of carboxymethyl cellulose (CMC) according to claim 4, wherein the functionalized carboxymethyl cellulose has the structure of (I): CMC functionalized with monovalent and divalent cations in, M + is a monovalent cation selected from the group consisting of sodium, potassium, and lithium; and M ++ is a divalent cation selected from the group consisting of calcium, magnesium, zinc, tin, and combinations thereof; as well as Where n≥2 to n≤2000, M + = 0.1 wt % to 10 wt % of the carboxymethyl cellulose, M ++ = 0.1 wt % to 7.5 wt % of the carboxymethyl cellulose.
14. The water-soluble salt of carboxymethyl cellulose (CMC) according to claim 4, wherein the functionalized carboxymethyl cellulose has the structure of (II): CMC functionalized with monovalent cations in, M + is a monovalent cation selected from the group consisting of sodium, potassium and lithium; wherein n≥2 to n≤2000, M + = 0.1 wt % to 10 wt % of the carboxymethyl cellulose.
15. The water-soluble carboxymethyl cellulose (CMC) according to claim 4, wherein the unit price (M + ) cation is selected from the group consisting of sodium, potassium and lithium.
16. The water-soluble carboxymethyl cellulose (CMC) according to claim 4, wherein the divalent (M ++ ) The cation is selected from the group consisting of calcium, magnesium, zinc, tin and combinations thereof.
17. The water-soluble carboxymethyl cellulose (CMC) according to claim 4, wherein the functionalized carboxymethyl cellulose (CMC) is in the form of dry powder.
18. The water-soluble carboxymethyl cellulose (CMC) according to claim 4, wherein the functionalized carboxymethyl cellulose (CMC) is (i) Calcium sodium carboxymethyl cellulose (Na + -Ca ++ -CMC), (ii) Sodium Magnesium Carboxymethyl Cellulose (Na + -Mg ++ -CMC), (iii) Sodium zinc carboxymethyl cellulose (Na + -Zn ++ -CMC), (iv) Carboxymethylcellulose sodium calcium zinc (Na + -Ca ++ -Zn ++ -CMC), (v) Carboxymethylcellulose sodium calcium magnesium (Na + -Ca ++ -Mg ++ -CMC), (vi) Carboxymethylcellulose sodium magnesium zinc (Na + -Mg ++ -Zn ++ -CMC), (vii) Sodium Tin Carboxymethyl Cellulose (Na + -Sn ++ -CMC), (viii) Carboxymethylcellulose sodium calcium tin (Na + -Ca ++ -Sn ++ -CMC), (ix) Carboxymethylcellulose sodium magnesium tin (Na + -Mg ++ -Sn ++ -CMC), or (x) sodium zinc tin carboxymethyl cellulose (Na + -Zn ++ -Sn ++ -CMC).
19. The water-soluble carboxymethyl cellulose (CMC) according to claim 6, wherein the functionalized carboxymethyl cellulose (CMC) is a combination of sodium carboxymethyl cellulose and at least one functionalized carboxymethyl cellulose (CMC) selected from the compounds of claims 18 (i) to (x) or a combination thereof.
20. The water-soluble carboxymethyl cellulose (CMC) according to claim 6, wherein the functionalized carboxymethyl cellulose (CMC) is sodium calcium carboxymethyl cellulose (Na + -Ca ++ -CMC) or sodium magnesium carboxymethyl cellulose (Na + -Mg ++ -CMC) or sodium zinc carboxymethyl cellulose (Na + -Zn ++ -CMC).
21. The water-soluble carboxymethyl cellulose (CMC) according to claim 6, wherein the functionalized carboxymethyl cellulose (CMC) is (i) sodium carboxymethyl cellulose (Na + -CMC) and (ii) (a) sodium calcium carboxymethyl cellulose (Na + -Ca ++ -CMC) or (b) sodium magnesium carboxymethyl cellulose (Na + -Mg ++ -CMC) or (c) sodium zinc carboxymethyl cellulose (Na + -Zn ++ -CMC).
22. The water-soluble carboxymethyl cellulose (CMC) according to claim 4, wherein the functionalized carboxymethyl cellulose (CMC) is used in oral care compositions, pharmaceutical compositions, home care compositions, industrial compositions, skin care compositions, food and nutritional health compositions, coating compositions, and oil and energy compositions.
23. The water-soluble carboxymethyl cellulose (CMC) according to claim 4, wherein the functionalized carboxymethyl cellulose (CMC) is used in an oral care composition selected from a mucoadhesive composition, a toothpaste / dentifogrum composition, an oral treatment composition, a mouthwash composition and a denture adhesive composition.
24. A mucoadhesive composition comprising: (i)(a) 0.1 wt % to 60 wt % of a water-soluble salt of carboxymethyl cellulose (CMC) according to claim 4, or (b) 0.1 wt % to 60 wt % of a water-soluble salt of carboxymethyl cellulose (CMC) according to claim 4 and at least one monovalent (M + ) a combination of cationically functionalized carboxymethyl cellulose (CMC); (ii) a maleic acid or maleic anhydride copolymer of 0.1 wt% to 60 wt% of a C1 to C4 alkyl vinyl ether and maleic acid or anhydride monomer, the copolymer being a substantially alternating structure of the monomers and 50 wt% to 90 wt% of the acid moieties in the polymer being converted to metal salts or mixed salts; and (iii) 0.1 wt % to 80 wt % of at least one additional ingredient.
25. The mucoadhesive composition of claim 24(i), wherein the water-soluble functionalized carboxymethyl cellulose (CMC) has a degree of substitution ranging from 0.4 to 1.
2.
26. The mucoadhesive composition of claim 24(i), wherein the water-soluble functionalized carboxymethyl cellulose (CMC) has a degree of substitution ranging from 0.4 to 0.
7.
27. The mucoadhesive composition of claim 24, wherein the functionalized carboxymethyl cellulose has a weight average molecular weight ranging from 2000 Daltons to 1,500,000 Daltons.
28. The mucoadhesive composition of claim 24, wherein: The maleic acid or maleic anhydride copolymer of C1 to C4 alkyl vinyl ether and maleic acid or anhydride monomer is a substantially alternating structure of monomers, and 50 wt % to 90 wt % of the acid portion in the polymer is converted into at least one monovalent cation (M + ) and at least one divalent cation (M ++ ) salt or mixed salt.
29. The mucoadhesive composition according to claim 28, wherein The maleic acid or maleic anhydride copolymer comprises maleic acid or maleic anhydride and C1 to C4 alkyl vinyl ether, wherein the predetermined weight average molecular weight of the maleic acid or maleic anhydride copolymer is about 500,000 to 3,000,000, and the maleic acid or maleic anhydride copolymer is prepared by the following method: in a solvent process or a solvent-free process, at about 50° C. to 150° C., in the presence of a free radical initiator, copolymerizing about 50 mol percent of maleic acid or maleic anhydride and about 50 mol percent of C1-C4 alkyl vinyl ether to produce uniform fine powder substantially free of residual maleic anhydride.
30. The mucoadhesive composition of claim 28, wherein the maleic acid or maleic anhydride and C1-C4 alkyl vinyl ether is a methyl vinyl ether-maleic acid copolymer or a methyl vinyl ether-maleic anhydride copolymer having a number average molecular weight of about 50,000 to about 500,000, wherein about 50% by weight to about 100% by weight of the carboxyl units in the polymer are converted to a mixture of metal salts selected from the group consisting of calcium, sodium, strontium, zinc, magnesium, iron, boron, aluminum, potassium, vanadium, chromium, manganese, nickel, copper, yttrium, titanium, and mixtures thereof.
31. The mucoadhesive composition of claim 29, wherein the salt of the methyl vinyl ether-maleic acid copolymer or methyl vinyl ether-maleic anhydride copolymer has a specific viscosity of about 2.5 to 5.0 when measured as a 1% w / v solution in methyl ethyl ketone (MEK) solution at 25°C.
32. The mucoadhesive composition of claim 29, wherein the methyl vinyl ether-maleic acid copolymer or methyl vinyl ether-maleic anhydride copolymer or a salt thereof comprises from about 18% to about 66% by weight of the composition.
33. The mucoadhesive composition of claim 29, wherein the methyl vinyl ether-maleic acid copolymer or methyl vinyl ether-anhydride copolymer has a weight average molecular weight of about 700,000 to about 3,000,000.
34. The mucoadhesive composition of claim 24, wherein the additional ingredient is selected from the group consisting of abrasives, anti-caking agents, antifungals, antimicrobials, anesthetics, antioxidants, antibiotics, anti-inflammatory agents, adhesives, buffers, colorants, cooling agents, dentin desensitizers, dispersants, enzymes, foaming agents, flavoring agents, fillers, fragrances, gelling agents, humectants, hydrophobic carriers, hydrophilic non-oil ingredients, preservatives, pigments, plasticizers, analgesics, sweeteners, thickeners, viscosity modifiers, excipients, surfactants, stabilizers, sensates, and mixtures thereof.
35. The mucoadhesive composition of claim 24, wherein the additional ingredient is selected from the group consisting of petrolatum, mineral oil, olive oil, vegetable oil, silicone, glycerin, polyethylene glycol, propylene glycol, polypropylene glycol, poly(ethylene oxide-propylene oxide) copolymers, diethylene glycol, triethylene glycol, sorbitol, water, and mixtures thereof.
36. The mucoadhesive composition of claim 24, wherein the mucoadhesive composition is a buccal composition, an oral composition, a vaginal composition, a nasal composition, a rectal composition, an ocular composition, a sublingual composition, a palatal composition, or a denture adhesive composition.
37. The mucoadhesive composition of claim 24, wherein the mucoadhesive composition is formulated as an ointment, lotion, liquid, solid, semisolid, emulsion, powder, dispersion, gel, patch, aerosol, or spray.
38. A denture adhesive composition comprising: (i)(a) 0.1 wt % to 60 wt % of a water-soluble salt of carboxymethyl cellulose (CMC) according to claim 4, or (b) 0.1 wt % to 60 wt % of a water-soluble salt of carboxymethyl cellulose (CMC) according to claim 4 and at least one monovalent (M + ) a combination of cationically functionalized carboxymethyl cellulose (CMC); (ii) a maleic acid or maleic anhydride copolymer of 0.1 wt% to 60 wt% of a C1 to C4 alkyl vinyl ether and a maleic acid or anhydride monomer, wherein the maleic acid or maleic anhydride copolymer is a substantially alternating structure of monomers and 50 wt% to 90 wt% of the acid moieties in the polymer are converted to metal salts or mixed salts; and (iii) 0.1 wt % to 80 wt % of at least one additional ingredient.
39. The denture adhesive composition of claim 38, wherein the water-soluble functionalized carboxymethyl cellulose (CMC) has a degree of substitution ranging from 0.4 to 0.
7.
40. The denture adhesive composition of claim 38, wherein the water-soluble functionalized carboxymethyl cellulose (CMC) has a degree of substitution ranging from 0.4 to 1.
2.
41. The denture adhesive composition of claim 38, wherein the functionalized carboxymethyl cellulose has a weight average molecular weight ranging from 2000 Daltons to 1,500,000 Daltons.
42. The denture adhesive composition of claim 38, wherein the maleic acid or maleic anhydride copolymer of a C1 to C4 alkyl vinyl ether and maleic acid or anhydride monomer is a mixed sodium and calcium salt of methyl vinyl ether and maleic anhydride having a specific viscosity of about 2.5 to 5.0 when measured as a 1% w / v solution in methyl ethyl ketone (MEK) solution at 25°C.
43. A toothpaste composition comprising: (i)(a) 0.1 wt % to 20 wt % of a water-soluble salt of carboxymethyl cellulose (CMC) according to claim 4, or (b) 0.1 wt % to 20 wt % of a water-soluble salt of carboxymethyl cellulose (CMC) according to claim 4 and at least one monovalent (M + ) a combination of cationically functionalized carboxymethyl cellulose (CMC); (ii) 0.1% to 60% by weight of an orally acceptable solvent or carrier selected from water, glycerin, sorbitol, propylene glycol, polypropylene glycol, PEG, ethylene oxide-propylene oxide polymers, or combinations thereof; (iii) 0.1 wt % to 20 wt % of a polymer of orally acceptable monomers including, but not limited to, maleic anhydride, maleic acid, C1 to C4 alkyl vinyl ethers, alkylene oxides, alkyl lactams, triglycerides, animal or vegetable oils, or combinations thereof, and (iv) 0.1 wt % to 80 wt % of at least one additional ingredient selected from the group consisting of an abrasive, an anti-caking agent, an active substance such as a fluoride providing compound, an antifungal agent, an antimicrobial agent, an anesthetic agent, an antioxidant, an antiplaque agent, an anti-tartar agent, an anti-biofilm agent, an anti-sensitivity agent, an anti-gingivitis agent, an anti- Vitamins, anti-inflammatory agents, adhesives, buffers, colorants, cooling agents, sedimentation agents, desensitizing agents, dispersants, sealants, enzymes, foaming agents, flavoring agents, fillers, fragrances, film-forming polymers, gelling agents, wetting agents, hydrophobic carriers, hydrophilic non-oil ingredients, mouthfeel agents, minerals, preservatives, peroxides, salts, pigments, pH regulators, plasticizers, analgesics, rheology modifiers, sweeteners, surfactants, stabilizers, sensitizers, detergents, antifouling agents, thickeners, viscosity regulators, excipients, vitamins, whitening agents, vegetable oils and animal oils or mixtures thereof, zinc salts of organic and inorganic acids or mixtures thereof.
44. The toothpaste composition according to claim 43, wherein (i) the thickener is selected from the group consisting of: (a) water-soluble cellulose ethers, such as sodium carboxymethylcellulose, sodium carboxymethylhydroxyethylcellulose and hydroxyethylcellulose, (b) vinylpyrrolidone polymers, for example N-vinylpyrrolidone, N-vinyl-2-pyrrolidone, N-vinyl-2-pyrrolidone and polyvinylpyrrolidone, (c) carboxyvinyl polymers (carbomers), (d) carrageenan, laponite and natural gums such as karaya, xanthan, guar, arabic and tragacanth, (e) colloidal magnesium aluminum silicate, hydrated silicon dioxide, thickened silicon dioxide or finely divided silicon dioxide, and (f) a homopolymer of acrylic acid crosslinked with an alkyl ether of pentaerythritol or an alkyl ether of sucrose; and (ii) The abrasive is selected from the group consisting of silicon dioxide, calcium carbonate, calcium bicarbonate, sodium carbonate and sodium bicarbonate.
45. A method for preparing a monovalent-divalent (M + -M ++ ) a method for producing carboxymethyl cellulose, the method comprising: (i) Preparation of (a) M ++ Chloride, M ++ Sulfate or M ++ an aqueous solution of a carbonate and (b) a C2-C4 alcohol; (ii) adding sodium carboxymethyl cellulose (M + ), and stirring the resultant at ambient temperature for at least 30 minutes; (iii) filtering the result of step (ii) to obtain a wet cake; (iv) stirring the wet cake from step (iii) in the hydroalcoholic solution for at least 30 minutes; (v) Repeat step (iv) at least 3 times to obtain pure M + -M ++ - wet cake of carboxymethyl cellulose; (vi) drying the wet cake from step (v) in a fluidized bed dryer at 50° C. to 70° C. for at least 15 to 30 minutes to obtain a dry M + -M ++ - carboxymethyl cellulose; and (vii) grinding the product obtained in step (vi) to separate M + -M ++ -Dry powder of carboxymethyl cellulose.
46. The method of claim 45, wherein the M + -M ++ - Carboxymethylcellulose is sodium calcium carboxymethylcellulose.
47. The method of claim 45, wherein the M ++ Chloride, M ++ Sulfate or M ++ The carbonate is calcium chloride, calcium sulfate or calcium carbonate.
48. The method of claim 45, wherein the C1-C4 alcohol is selected from the group consisting of methanol, ethanol, propanol, isopropanol, and butanol.
49. The method of claim 45, wherein the grinding is carried out in a mill using 0.75 mm, 0.20 mm and 0.08 mm screens.
50. The method of claim 45, wherein the dry powder has an average particle size ranging from 20 microns to 300 microns.
Citation Information
Patent Citations
Denture stabilizer
US20050032940A1
Antibacterial antiplaque oral composition
US5334375A
Desensitizing anti-tartar dentifrice
US5505933A
Antiplaque antibacterial oral composition
US5776435A